Siphysio: um serious game para simulação de atendimento em fisioterapia ortopédica e traumatologia - CRUZ, Igor Moura da (2024)
The present work documents the development of the Serious Game SIPHYSIO, a game focused on physiotherapy, with a focus on traumatology and orthopedics. The main objective is to provide a ludic and immersive learning experience for physiotherapy students, as well as to offer a training tool for professionals in the field. The project is motivated by the need to adapt to market demands and to use interactive technologies to improve the teaching and learning process in the health area.